Didactic Possibilities of Developing Professional Competence of Future Primary School Teachers in the Context of Dual Education - Umurov Zarif Latifboyevich (International Journal on Integrated Education, 2026)
This article analyzes the didactic possibilities of developing professional competence of future primary school teachers in the context of dual education. The study highlights the role of the dual education model, based on the integration of theory and practice, in improving the effectiveness of pedagogical training. It substantiates the mechanisms for forming professional competence through practice-oriented methods, cooperation between higher education institutions and schools, reflective analysis, and innovative approaches. As a result, it is proven that dual education serves as an effective didactic system for developing the motivational, cognitive, practical, and communicative competencies of future teachers.